Assessment of Behavioral disorders of children with Autism - Kawther S. Dawood; Ali K. Khudhair (Kufa Journal for Nursing Sciences)
Background: Autistic disorder is a neurological disorder that causes a broad area of behavior impairments in children, including: hyperactivity, short attention span, impulsivity, aggressiveness, self – injurious behavior, tempers tantrum and abnormalities of eating or sleeping may be found. There is an increased rates of autism reached to 10-17% per year. It is the fastest-growing serious developmental disability in the worldwide over the past decades.